Involving farmers in the development process to improve adoption of varieties developed by National Maize-Breeding Programs - Ransom, J.K.; Koirala, Keshab Babu; Rajbhandari, N.; Adhikari, K. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Developing maize varieties that will be readily adopted by subsistence farmers is challenging as there are numerous characteristics in addition to agronomic performance that are important to these farmers. Furthermore, these preferences vary from location to location. it may be logical lo conclude that because of these location-specific requirements, maize breeding that targets subsistence farmers should be done at a localized level. National maize-improvement programs have an important role to play in developing improved maize genotypes for these farmers because they have access to a wide range of genetic materials that allows for Ihe identification of genes for disease resistance and high yield that may not be available in local germplasm. Furthermore, they have the expertise required to incorporate these genes efficiently into genotypes that meet the farmers' other requirements. To increase the impact of genotypes developed by national maize-improvement programs, however, farmer input into their activities is essential. A balance between on-Station breeding activities and interactions with farmers is needed in order for the process to be efficient. Therefore, the National Maize Research Program within Nepal', National Agricultural Council (NARC) has developed the following procedures for developing maize genotypes for subsistence farmers with their input. First, through on-farm surveys, Ihe required grain (i,e., flint, dent, yellow, or white) and plant (i,e., tall ,leafy, early, or late, etc.) types are determined Second, exotic and locally developed genotypes are screened for the desired characteristics and general adaptation on-station using local varieties from the targeted environment as checks to ensure that maturity duration matches that already used by farmers. Promising materials are initially tested on-station for yield and disease resistance. Elite materials (approximately six to eight genotypes) are then tested in on-farm trials under farmers' conditions. Farmers who grow these materials observe their agronomic performance and provide input about which entries they prefer. Only those varieties that have proven to be high yielding and stable, and which have the characteristics preferred by farmers, will be released and made available on a more national scale. Maintenance of released genotypes and seed multiplication is a resource-intensive activity that must be limited to genotypes that are Ihe most likely to have an impact we believe that this varietal-development scheme will efficiently provide new and desirable options to small-scale subsistence maize farmers in Nepal.